Dual band dipole antenna with harmonic suppression capability - Albishti, Abobaker A Mohammed (2015)
Wireless communication system has become very popular, and has been developed rapidly over last one and a half decade. Wireless devices that operate in multiband frequencies, with smaller size, are now used by almost everyone. In this work, multiband dipole antenna with harmonic suppression capability has been designed. The dual-band dipole antenna has been vigorous, since it is simple, easy to be designed and fabricated. However, higher order modes (HOM) in these multiband antennas gives problems when designing such type of antennas. The proposed antenna consists of two designs; first design is building single parasitic element which generates 0.8 GHz, 2.4 GHz and 4 GHz; while the second design was realized by adding three parasitic elements on both sides of the two arms of the design with same frequencies of the first design which generates another frequency component of 5.1 GHz. They are named as MDA1PE and MDA3PE, respectively. The unwanted frequencies have been suppressed by adding the stub. The first design has successfully eliminated frequency component of 4 GHz , while the second design has suppressed frequencies of 4 GHz and 5.1 GHz. The suppression leads to elimination of possible noise interference through removing the unwanted frequencies. Hence, the final design is dual band (0.8 GHz and 2.4 GHz) dipole antenna which is free from noise interference. The proposed concept has been investigated through simulation in CST Microwave studio and actual experimental works. The simulation and experimental results confirm the validity of the proposed antenna. There have been matching agreements between both simulation and measurements results.